Components of Pearson's Statistic for at Least Partially Ordered m-Way Contingency Tables. (26th October 2009) - Rayner, J. C. W.; Beh, Eric J.
Abstract : For at least partially ordered three-way tables, it is well known how to arithmetically decompose Pearson'sX P 2 statistic into informative components that enable a close scrutiny of the data. Similarly well-known are smooth models for two-way tables from which score tests for homogeneity and independence can be derived. From these models, both the components of Pearson'sX P 2 and information about their distributions can be derived. Two advantages of specifying models are first that the score tests have weak optimality properties and second that identifying the appropriate model from within a class of possible models gives insights about the data. Here, smooth models for higher-order tables are given explicitly, as are the partitions of Pearson'sX P 2 into components. The asymptotic distributions of statistics related to the components are also addressed.